EARLY CHILDHOOD EDUCATIONHEAD LEADERSHIP IN IMPLEMENTING ISLAMIC VALUES-BASED CHARACTER LEARNING - Fijriyani, Puja; Arifin, Imron; Juharyanto, Juharyanto (International Education Trend Issues, 2023)
The research was conducted to determine the leadership of the Early Childhood Education head in instilling Islamic values-based character learning. The formation of character with Islamic values is learning given in early childhood to form a personality with good moral values following Islamic teachings. This study uses a descriptive qualitative approach. The design of this study is a multi-site design at two schools in Pamekasan Regency, namely Al-Uswah IT Kindergarten and Al-Ghazali Kindergarten. The two Early Childhood Education schools both apply character learning with Islamic values. The technique used by researchers in collecting data was conducting in-depth interviews with Early Childhood Education heads in two schools, participatory field observations, and documentation studies to support the completeness of the research data. The results of this study indicate that Al-Uswah IT Kindergarten and Al-Ghazali Kindergarten both apply character learning with Islamic values, namely responsibility, curiosity, discipline, independence, and respect for achievement. (1) this responsibility is proven by taking toys and storing their play equipment in a place that has been prepared; (2) curiosity is shown by the teacher conveying a material either by telling a story or otherwise so that it stimulates children to ask questions about things they don't understand and answer questions from the teacher; (3) discipline, children are educated to be disciplined in carrying out habits in a class by lining up before entering class, reading prayers as a habit before learning; (4) independent, children are accustomed to carrying out their needs without the help of the teacher, for example in storing their shoes or bags in a place provided by the school; and (5) appreciating achievement, the teacher provides motivation and encouragement to children by applauding their courage and the confidence to tell stories in front of the class or appreciate other achievements